THE CORELATION BETWEEN STRESS AND COFFEE CONSUMPTION ON GASTRITIS IN THE HEALTH CENTER WORKING AREA PONDOK BENDA, BANTEN - Akub Selvia; Agustina Chriswinda Bura Mare (Jurnal Ilmu Keperawatan Medikal Bedah, 2026)
Indonesian health profile data in 2022 revealed that there were 30,154 cases of gastritis and included in the top ten diseases among sick people in Indonesian hospitals. Predisposing factors in the occurrence of gastritis are respondent characteristics, stress, and coffee consumption patterns. This study is a quantitative study that uses primary data (questionnaires) and uses cross-sectional research methods. The aim of this study is knowing the relationship between the stress and coffee consumption to gastritis. The sampling technique in this study used Purposive Sampling with a total sample size of 172 early adults in the Pondok Benda Health Center working area. The results of this study found that there was a relationship between stress and the incidence of gastritis (p-value = 0.037, < 0.05) and there was a relationship between coffee consumption and the incidence of gastritis (p-value = 0.024, < 0.05). Conclusion in this study is there was a relationship between stress and coffee consumption patterns to the incidence of gastritis.